Impact of a new pesticide on rhizosphere microbes and plant health: Case study of Y17991 against sharp eyespot in wheat - Xiangxia Yang; Tingting Chen; Libo Xiang; Limin Liu; Mi Wei (Journal of Integrative Agriculture, 2025)
Sharp eyespot (Rhizoctonia cerealis) is a widespread soil-borne fungal disease that poses a severe threat to wheat health, and it is one of the main obstacles to achieving stable and high-quality wheat yields in China. Our collaborative team has developed a novel, efficient, and low-toxicity fungicide named Y17991 (N-(2-(2,4-bis-(trifluoromethyl)phenoxy)phenyl)-3-(difluoromethyl)-1-methyl-1H-pyrazole-4-carboxamide). Preliminary laboratory tests confirmed the significant inhibitory effect of this agent on R. cerealis. Large-area field trials also demonstrated its efficacy, with a disease prevention index of 83.52%, which is 1.97% greater than that of the widely used thifluzamide, and it significantly increased the wheat yield. Moreover, this study explored the impacts of Y17991 on the structure and function of the microbial community in wheat rhizosphere soil. Bacterial communities were more strongly affected than fungal communities. Y17991 significantly modulated key amino acid metabolic pathways and certain biosynthetic processes in diseased wheat rhizospheres, and it also enhanced certain biosynthetic pathways and metabolic activities in healthy wheat rhizospheres. Additionally, the application of Y17991 regulated rhizosphere metabolites, thus exerting significant control over the microbial community. We identified 15 microbial strains potentially involved in the prevention and treatment of R. cerealis, and Y17991 treatment promoted the growth of Pedobacter and Bacillus strains. These strains not only aid in plant growth but they also have the potential for disease prevention. In summary, Y17991 application at a reasonable dose does not cause significant disruption to nontarget rhizosphere microbial communities. In future studies, we will continue to investigate the impacts of Y17991 on nonmicrobial components in soil ecosystems, such as protozoa and nematodes. Our research provides a theoretical basis for the scientific application and promotion of new fungicides and offers a significant reference for establishing a comprehensive system for assessing the ecological impact of pesticides on the environment.